Identity abuse against sexual and gender minority communities: The Being LGBTQI+ in Ireland study - Carmel Downes; Karin O’Sullivan; Jan de Vries; Matt Kennedy; Renee Molloy; Aviejay Paul; Agnes Higgins (PLoS ONE, 2025)
Identity abuse targets people on the basis of immutable characteristics, and has the potential to cause greater emotional and psychological distress for this reason. People with multiple intersecting identities may be at greater risk. While the LGBTQI+ population experience higher rates of abuse than the general population, studies often focus on one type of abuse and rarely examine within LGBTQI+ group variation. A national cohort study involving over 2,800 LGBTQI+ participants aged 14 + examined the prevalence and predictors of LGBTQI+ identity abuse across six forms of abuse, as well as experiences of identity abuse more broadly via an open-ended question. Lifetime and past year prevalence of at least one form of abuse was 79% and 42% respectively. Polyvictimisation (two or more forms of abuse) was experienced by over half of the sample within their lifetime. Besides LGBTQI+ identity abuse, participants also experienced other forms of identity abuse, including ableism, racism, and sexism. LGBTQI+ people with disability were particularly at risk of abuse. Asexual and bisexual participants had lower odds of many forms of identity abuse. Risk, however, was constituted differently across the different forms of abuse, highlighting the importance of not siloing abuse in research by examining each type independently of one another. Interventions to tackle prejudice-based abuse are required, including those that address heteronormative and gender normative assumptions that seem to underpin prejudice, as well as tackling ageism and racism. Polices and measures to safeguard LGBTQI+ people against identity abuse also need to be enacted.